2004
DOI: 10.2202/0027-6014.1353
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Boulder Uphill: The Persistence of First-Generation College Students

Abstract: This study examined the impact of background, aspirations, achievement, college experiences, and price on the persistence of first-generation (F-gen) and continuing generation (C-gen) college students at 4-year institutions using the National Postsecondary Student Aid Study of 1995–96 (n = 24,262). We found differences between the two groups on the effect size for almost all of the significant variables. F-gen students were more sensitive to financial aid and averse to student loans than their peers. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Rising tuition has created bigger obstacles for students, especially those charged with financing their own education. Other researchers (Lohfink & Paulsen, 2005;Somers, Woodhouse, & Cofer, 2004) found that increases in financial aid improved the likelihood that first generation students will persist in college, but increases in loan debt make it much more likely that they will depart without graduating.…”
mentioning
confidence: 99%
“…Rising tuition has created bigger obstacles for students, especially those charged with financing their own education. Other researchers (Lohfink & Paulsen, 2005;Somers, Woodhouse, & Cofer, 2004) found that increases in financial aid improved the likelihood that first generation students will persist in college, but increases in loan debt make it much more likely that they will depart without graduating.…”
mentioning
confidence: 99%
“…Thus, additional research should consider including students at different stages of their college career (e.g., transfer students) to determine if subsequent support from family has a different impact on graduation goals. Another characteristic of the sample to consider is many of the students included were first-generation college students, and there has been mixed findings on how firstgeneration status affects student persistence (e.g., Duggan, 2001;Somers, Woodhouse, & Cofer, 2004). Using institutional data Ishitani (2003) discovered a higher risk of departure among first-generation students in their first year of college.…”
Section: Limitationsmentioning
confidence: 99%
“…Financial aid is a constant worry for first-generation college students (Bui, 2002) and so increasing the availability of financial aid for first-generation college students could help alleviate some of the concerns and pressures they face. In order to help retain first-generation college students, financial aid is crucial (Somers, Woodhouse, & Cofer 2004). Somers, Woodhouse, and Cofer (2004) identify two reasons why the study of firstgeneration college students and federal financial aid is important for success.…”
Section: Financial Aidmentioning
confidence: 99%
“…In order to help retain first-generation college students, financial aid is crucial (Somers, Woodhouse, & Cofer 2004). Somers, Woodhouse, and Cofer (2004) identify two reasons why the study of firstgeneration college students and federal financial aid is important for success. First, there has been a shift from federal grants to student loans as the main source of financial aid.…”
Section: Financial Aidmentioning
confidence: 99%